2022
DOI: 10.1136/bmjopen-2021-050610
|View full text |Cite
|
Sign up to set email alerts
|

Results of a pilot feasibility randomised controlled trial exploring the use of an electronic patient-reported outcome measure in the management of UK patients with advanced chronic kidney disease

Abstract: ObjectivesThe use of routine remote follow-up of patients with chronic kidney disease (CKD) is increasing exponentially. It has been suggested that online electronic patient-reported outcome measures (ePROMs) could be used in parallel, to facilitate real-time symptom monitoring aimed at improving outcomes. We tested the feasibility of this approach in a pilot trial of ePROM symptom monitoring versus usual care in patients with advanced CKD not on dialysis.DesignA 12-month, parallel, pilot randomised controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…An evaluation of this intervention in routine practice is planned. The RePROM pilot trial demonstrated the feasibility of a RCT of ePRO symptom monitoring in patients with advanced CKD 10 . The intervention comprised real-time integration of ePRO symptom data into the electronic health record with automated alerting of the clinical team when participants reported severe symptoms.…”
Section: Current Use and Evidence Of Benefitmentioning
confidence: 99%
“…An evaluation of this intervention in routine practice is planned. The RePROM pilot trial demonstrated the feasibility of a RCT of ePRO symptom monitoring in patients with advanced CKD 10 . The intervention comprised real-time integration of ePRO symptom data into the electronic health record with automated alerting of the clinical team when participants reported severe symptoms.…”
Section: Current Use and Evidence Of Benefitmentioning
confidence: 99%
“…Studies from North America demonstrate the feasibility of ePRO collection in haemodialysis (HD) settings,16 19 20 while the Australian Symptom monitoring With Feedback Trial21 and Canadian EMPATHY studies22 are cluster randomised controlled trials exploring the usefulness of integrating PRO assessments in the clinical management of patients receiving HD. In advanced CKD populations, the use of an electronic Patient-Reported Outcome Measure in the Management of Patients with Advanced CKD (RePROM) study in the UK piloted the use, and established feasibility, of an ePRO for remote symptom monitoring in real time 9 23. The AmbuFlex telepro system is used in practice to manage renal outpatient follow-up in Denmark and as a complimentary tool in consultations24 25 and is currently being evaluated through the PRO-KID trial: a non-inferiority pragmatic randomised controlled trial investigating the effectiveness of the quality of care, use of resources and patient outcomes associated with PRO-based follow-up in patients with CKD 24…”
Section: Introductionmentioning
confidence: 99%